Ludo History (Dory) dalam pembelajaran sejarah di SMA negeri 7 Bandung (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This research emerged from researcher concern regarding student’s lack of conceptual comprehension at Grade 11 Social Science 3 - Senior Highschool 7 Bandung. The indicator to measure conceptual understanding in this research is to read the trusted source about the contents, knowing the concepts, explaining the concepts, analogizing the concepts, classifying the concepts, and connecting the concepts. This research used the classroom action research designed by Kemmis and McTaggart which consists of four stages: planning, acts, observation and reflection. According to result analysis, there is an increase on every cycle in the student’s development to reach the criteria of concept comprehension indicator, this can be seen by looking at the scores on every indicator in each cycle. Therefore, it shows the achievement when applying a game called “Ludo History” in increasing student’s conceptual understanding. Moreover, by looking at the results, the game Ludo History (Dory) can become one of the alternatives to learning problems in the classroom.
Keywords: Classroom Action Research; Conceptual Comprehension; Ludo History (Dory)